Screening of Prevalence HBV and HCV from first six months of 2020 in Erbil province Kurdistan region /Iraq - harem othman smail (Hasanuddin University, 2021)
Nowadays, infections of the HBV and HCV are one of the major global public health problem. The objective of this study was to determine the prevalence of HBV and HCV virus from the first six months of 2020 in the of Erbil province, Kurdistan region of Iraq. Also associations between the prevalence of HBV and HCV in different age groups, has been established. The study was conducted on (101) individuals (63 males and 38 females), of different aged population groups, in Erbil city from beginning of January 2020 to the end of June 2020. To detect the positive results of both HBV and HCV (VL), all samples subjected to detect their viral load by GeneXpert (RT PCR or RTqPCR). Out of (101) samples, 24(%23.76) of HBV and 7(%6.93) for HVC in both sex were detect positive respectively. Prevalence of both HBV and HCV was highest in males than females. Also the highest percentage of HBV found between (19-40) years, 12(%19.04) in males and 5(%13.15) in females. In addition highest number of HCV positive was found between (41-60) years, which 2(%3.17) and 2(%5.26) for males and females respectively, while opposite results were found from other aged groups